2008
DOI: 10.1186/bcr1998
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and prognostic value of Bag-1 and Bcl-2 in breast cancer

Abstract: Introduction Bcl-2 antanogene-1 (Bag-1) binds the antiapoptotic mediator Bcl-2, and enhances its activity. Bcl-2 and Bag-1 are associated with chemotherapy resistance in cancer cells. Drugs that target Bcl-2 are currently in clinical development. The purpose of the present study was to examine expression patterns of Bag-1 in a large cohort of breast tumors and to assess the association with Bcl-2, estrogen receptor, progesterone receptor and Her2/neu, and other clinical/ pathological variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 68 publications
4
53
0
Order By: Relevance
“…So far, the strongest predictive and prognostic factor has been the number of affected lymph nodes (Munster and Norton, 2001), yet within the lymph node-positive subset and the lymph node-negative subset of patients there is variability in prognosis (Nadler et al, 2008). In this study, Bcl-2 was more frequently associated with negative nodal status (100%) in both TNBC and non-TNBC and there was a significant inverse correlation with nodal positivity in non-TNBC group.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…So far, the strongest predictive and prognostic factor has been the number of affected lymph nodes (Munster and Norton, 2001), yet within the lymph node-positive subset and the lymph node-negative subset of patients there is variability in prognosis (Nadler et al, 2008). In this study, Bcl-2 was more frequently associated with negative nodal status (100%) in both TNBC and non-TNBC and there was a significant inverse correlation with nodal positivity in non-TNBC group.…”
Section: Discussionmentioning
confidence: 51%
“…On the other hand, Nadler et al (2008), found no association between expression of Bcl-2 and patient's age.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although these experiments were primarily focused on the role of BAG-1 in the development of the malignant process in the breast, it is nonetheless of interest to speculate how they may relate to the association between high BAG-1 expression and improved outcome for breast cancer patients observed by us and others (Turner et al, 2001;Cutress et al, 2003;Millar et al, 2008;Nadler et al, 2008). One possible explanation for this apparent dichotomy lies in the inherent heterogeneity in BAG-1's actions, such that its pro-survival effects may have an important role during tumor initiation, but lead to the formation of a less aggressive or more therapeutically responsive cancer, for example, through its known effects on nuclear hormone receptor function.…”
Section: Discussionmentioning
confidence: 99%